2012
DOI: 10.1038/cddis.2012.85
|View full text |Cite
|
Sign up to set email alerts
|

Photofrin binds to procaspase-3 and mediates photodynamic treatment-triggered methionine oxidation and inactivation of procaspase-3

Abstract: Diverse death phenotypes of cancer cells can be induced by Photofrin-mediated photodynamic therapy (PDT), which has a decisive role in eliciting a tumor-specific immunity for long-term tumor control. However, the mechanism(s) underlying this diversity remain elusive. Caspase-3 is a critical factor in determining cell death phenotypes in many physiological settings. Here, we report that Photofrin-PDT can modify and inactivate procaspase-3 in cancer cells. In cells exposed to an external apoptotic trigger, high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…This, together with our previous finding that Photofrin binds procaspase-3 and mediates its PDT-triggered Met oxidation and inactivation 29 , prompted us to search for additional Photofrin-binding proteins in human cells. We hypothesized that such proteins might be more susceptible to oxidative damage during Photofrin-mediated PDT.…”
Section: Resultsmentioning
confidence: 98%
“…This, together with our previous finding that Photofrin binds procaspase-3 and mediates its PDT-triggered Met oxidation and inactivation 29 , prompted us to search for additional Photofrin-binding proteins in human cells. We hypothesized that such proteins might be more susceptible to oxidative damage during Photofrin-mediated PDT.…”
Section: Resultsmentioning
confidence: 98%
“…While 18 O and 15 N labeling have been exploited to elucidate mechanistic aspects of PDT, the natural 31 P abundance of phosphine traps has not been explored in depth yet, as done here in a PDT relevant project.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that PDT relies on the generation of ROS 12 13 14 15 . Our study also detected abundant intracellular and extracellular ROS generation after DVDMS-PDT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit remarkable photophysical properties, including high stability, water-solubility, high phototoxicity, and low dark toxicity 8 9 10 . Porfimer sodium (Photofrin II) was the first photosensitizer approved by the US Food and Drug Agency and has already been applied clinically to treat various cancers and non-cancer diseases 11 12 13 14 . However, patients treated with Photofrin II suffer from a skin photosensitivity, requiring protection from sunlight or bright lights exposure for up to 3 months 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation